Sistem Pendukung Keputusan Penentuan Kenaikan Jabatan Pegawai di RS. Sultan Sulaiman dengan Metode Profile Matching - Tengku Muhammad Rizal; R. Mahdalena Simanjorang (Pustaka Timur Publisher, 2021)
The development of technology makes human work easier and more effective. Technology has penetrated almost every field, both in everyday life and in the field of human work. The role of technology in various aspects of activities can be understood because technology can facilitate the resolution of a problem by using a computer system, especially using a decision support system. Technological developments have entered institutions such as the Sultan Sulaiman hospital institution. The existence of technology at Sultan Sulaiman Hospital can assist the hospital in making decisions based on existing data. This study discusses the determination of the promotion of employees at the hospital. Sultan Sulaiman with Profile Matching Method. In this study, 10 samples of honorary employees at the Sultan Sulaiman Hospital were used to be used as candidates for promotion. The data used consists of Full Name Using Title, Gender, Place, Date of Birth, and Job Description. This system is built using the scripting language PHP and MYSQL as the database. Based on the calculation results, it can be concluded that the names of the employees who will be promoted to the position of the medical team leader are Arbaiyah, Amd.Ft (A2) with a score of 8.87778 who is ranked 1st and Citra Dewi Nasution, Amd (A7) with a score of 8.86 which ranked 2. The level of accuracy of the profile matching method is quite high. The program that is built is dynamic.